THE PATTERN OF ISLAMIC CHARACTER EDUCATION OF THE MUHAMMADIYAH STUDENT ASSOCIATION (IMM) AND ITS IMPLEMENTATION IN FORMAL EDUCATION - Kadar Risman; A Asman (Profetika: Jurnal Studi Islam, 2022)
Education is not only the task of educational institutions. the duties of all components of the nation’s children, including student organizations such as IMM. The purpose of this study was to describe the pattern of character education carried out by IMM for Kendari City students who also helped improve the world of education. This research is afield research using qualitative methods to describe the pattern of IMM character education. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis using data reduction, data presentation, and data lever. The results of this research are that there are three patterns of IMM character education, namely the Formal Cadre (education) pattern, the halaqah or teaching pattern (tarbiyah) and the sustainable development pattern. The three of them can have implications for formal education in school institutions.